Doping carbon electrodes with sulfur achieves reversible sodium ion storage. (2nd March 2023) - de Tomas, Carla; Alabidun, Sarat; Chater, Luke; Darby, Matthew T; Raffone, Federico; Restuccia, Paolo; Au, Heather; Titirici, Magda M; Cucinotta, Clotilde S; Crespo-Ribadenyra, Maria
Abstract: We present a combination of experiments and theory to study the effect of sulfur doping in hard carbons anodes for sodium-ion batteries. Hard carbons are synthesised through a two step process: hydrothermal carbonisation followed by pyrolysis of a biomass-derived carbon precursor. Subsequent sulfur doping is introduced via chemical-vapour deposition. The resulting sulfur-doped hard carbon shows enhanced sodium storage capacity with respect to the pristine material, with significantly improved cycling reversibility. Atomistic first principles simulations give insight into this behaviour, revealing that sulfur chemisorbed onto the hard carbon increases the sodium adsorption energies and facilitates sodium desorption. This mechanism would increase reversible Na storage, confirming our experimental observations and opening a pathway towards more efficient Na-ion batteries.